BBM-added bamboo powder biodegradable material and application thereof in beer bottles
By blending BBM bamboo powder with specific polymers and using nano-titanium dioxide modification technology, the shortcomings of beer bottle materials in terms of mechanical strength and UV aging resistance are solved, and tougher and durable beer bottle materials are achieved, while having good biodegradation performance.
Patent Information
- Application Number
- CN202510022156.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2045-01-07
AI Technical Summary
The existing beer bottle materials have shortcomings in terms of mechanical strength and UV aging resistance, which is difficult to meet the needs of beer bottles.
BBM bamboo powder is blended with polyadipic acid-butylene terephthalate and polybutylene succinate to improve the compatibility of bamboo powder by low-temperature oxygen plasma treatment and ultrasonic treatment, and nanotitanium dioxide is formed by template method to enhance the anti-aging performance of the material.
It significantly improves the mechanical properties and UV aging resistance of beer bottle materials, making them tougher and durable during use, and has good biodegradability.
Smart Images

Figure CN119613929A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biodegradable materials, in particular to a biodegradable material added with BBM bamboo powder and application thereof in beer bottles. Background Art
[0002] my country is a major beer producer and consumer, and the beer packaging market is vast. Existing beer packaging mainly includes glass bottles and metal cans. Glass bottles are the main packaging containers. Glass has very good chemical inertness and stability, and almost does not interact with any contents. However, glass bottles have low impact strength. Especially when the surface is damaged, there is a risk of explosion and injury after filling with beer. At the same time, they are heavy, inconvenient to carry, and have high transportation costs.
[0003] Plastic bottles have excellent properties, such as high strength, high transparency, light weight, and are not easy to break. At present, materials such as polycarbonate and polyethylene terephthalate have greatly improved in terms of barrier properties, which can basically meet the requirements of beer packaging. They have been widely used as packaging bottles for carbonated beverages and drinking water. These plastics have also been used in beer bottles abroad, but they are not easy to degrade and are easy to pollute the environment after being discarded.
[0004] Bamboo powder is a renewable biomass resource. Bamboo Biodegradable Material (BBM) using bamboo powder as the main raw material is the best choice for biodegradable products. It is degraded under natural conditions through the life activities of soil microorganisms. As a green renewable resource, it has good biodegradability and biocompatibility, but its texture is brittle and its UV resistance is poor, which limits its use.
[0005] How to blend bamboo powder with polybutylene succinate for use in beer bottles, while improving the mechanical strength of the beer bottles and enhancing their resistance to UV aging to ensure their performance, has become a technical problem that needs to be solved. Summary of the invention
[0006] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a biodegradable material with added BBM bamboo powder and its application in beer bottles.
[0007] A biodegradable material with BBM bamboo powder added. The raw materials thereof include, by mass, 10-20 parts of bamboo powder, 10-30 parts of polybutylene adipate-terephthalate, 10-20 parts of polybutylene succinate, 1-3 parts of dopamine hydrochloride, 0.1-0.5 parts of n-butylamine, 1-2 parts of hexadecyltrimethylammonium bromide, 1-5 parts of tetraethyl orthosilicate, 1-2 parts of tetrabutyl titanate, 1-2 parts of 3-aminopropyltriethoxysilane, 1-2 parts of an antioxidant and 1-2 parts of a plasticizer.
[0008] Preferably, the antioxidant is at least one of antioxidant BHT, antioxidant DNP, antioxidant DLTP, antioxidant 1010, and antioxidant 168.
[0009] Preferably, the plasticizer is at least one of disproportionated rosin, epoxidized soybean oil, dibutyltin dilaurate, acetyl tributyl citrate, and tricresyl phosphate.
[0010] Preferably, the mesh size of the bamboo powder is 1000-2000 mesh.
[0011] Preferably, the bamboo powder is obtained by crushing, extracting, filtering, concentrating, refining and purifying, drying and crushing moso bamboo with an age of 3-3.5 years.
[0012] The method for preparing the biodegradable material with added BBM bamboo powder comprises the following steps: S1. Treat bamboo powder with low-temperature oxygen plasma for 5-15 seconds, with the treatment power of oxygen plasma being 100-150W, then add it and dopamine hydrochloride into Tris-HCl buffer, perform ultrasonic treatment for 1-2 hours, adjust the pH value of the system to 7.5-8.5, stir at 60-80° C. for 10-15 hours, centrifuge, wash, and vacuum dry to obtain pretreated bamboo powder; S2, adding n-butylamine and hexadecyltrimethylammonium bromide to water, stirring at 80-90°C for 10-20min, adding tetraethyl orthosilicate thereto and continuing stirring for 10-30min, adding tetrabutyl titanate thereto and continuing stirring for 1-2h, centrifuging, washing, adding methanol and concentrated hydrochloric acid, reflux in an oil bath for 1-2h, centrifuging, washing with ethanol, vacuum drying, sending into a tubular furnace for calcination, adding 3-aminopropyltriethoxysilane and anhydrous ethanol, stirring at 40-50°C for 1-2h, centrifuging, washing, and vacuum drying to obtain activated titanium dioxide; S3, mixing polybutylene adipate-terephthalate, polybutylene succinate, pretreated bamboo powder, activated titanium dioxide, antioxidant and plasticizer, and extruding.
[0013] Preferably, in S1, the concentration of Tris-HCl buffer is 0.01-0.05 mol / L.
[0014] Preferably, in S1, the ultrasonic frequency is 5-15 kHz.
[0015] Preferably, in S2, the calcination temperature is 550-600°C, and the calcination time is 2-4h.
[0016] The above-mentioned biodegradable material with added BBM bamboo powder is used as beer packaging material. Beneficial Effects
[0017] 1. Due to the low specific gravity and high humidity of traditional bamboo powder, it cannot be directly used for adding and modifying plastic materials. In the present invention, bamboo powder is prepared from moso bamboo, and then polydopamine is combined on its surface after activation, which can effectively reduce the polarity of bamboo powder and enhance the interfacial compatibility with polybutylene adipate-terephthalate and polybutylene succinate. The prepared biodegradable material has good toughening effect and good mechanical properties. However, it has the defects of poor anti-aging effect and easy degradation under long-term exposure to ultraviolet rays.
[0018] 2. The present invention adopts a template method to form nano titanium dioxide. After the amination treatment, the surface energy of titanium dioxide nanoparticles can be effectively reduced, and the dispersion performance between polybutylene adipate-terephthalate, polybutylene succinate, and pretreated bamboo powder can be increased. The agglomeration of titanium dioxide is effectively avoided, and it can be evenly dispersed in the matrix. With the effect of nano silicon dioxide, the specific surface area is very high, and the contact area with the polymer matrix can be effectively increased. Not only can the interface defects with the polymer matrix be reduced, but also the strengthening and toughening effect is excellent. At the same time, the anti-ultraviolet aging performance is good, and it has an excellent prospect for being used in beer bottles.
[0019] 3. The present invention effectively improves the dispersibility and compatibility of bamboo powder in polybutylene succinate, effectively improves the mechanical properties of BBM, makes the obtained BBM have excellent mechanical properties, and at the same time improves the anti-ultraviolet strength of the degradable material to a certain extent. The moso bamboo of the present invention has a wide source and is easy to obtain, grows fast, is green and environmentally friendly, can be buried in the soil after use, can be quickly decomposed, and has good biodegradability. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a comparison chart of the tensile strength of the biodegradable materials obtained in Example 5 and Comparative Examples 1-2 and the tensile strength retention rate after UV aging.
[0021] Figure 2 It is a comparison chart of the flexural strength and the flexural strength retention rate after UV aging of the biodegradable materials obtained in Example 5 and Comparative Examples 1-2.
[0022] Figure 3 It is a comparison chart of the notched impact strength and the notched impact strength retention rate after UV aging of the biodegradable materials obtained in Example 5 and Comparative Examples 1-2.
[0023] Figure 4 This is a comparison chart of the weight loss rate of the biodegradable materials obtained in Example 5 and Comparative Examples 1-2 after being buried in the soil for 60 days and the number of days required for complete degradation. DETAILED DESCRIPTION
[0024] The present invention will be further explained below in conjunction with specific embodiments.
[0025] The bamboo powder used below is produced by the applicant using 3-3.5 year old bamboo through a multi-step process of crushing-extraction-filtration-concentration-refining and purification-drying-re-crushing, and then passed through a 500-mesh sieve. Example 1
[0026] A biodegradable material with BBM bamboo powder added, the raw materials of which include: 10g of polybutylene adipate-terephthalate, 10g of polybutylene succinate, 10g of bamboo powder, 1g of dopamine hydrochloride, 0.1g of n-butylamine, 1g of hexadecyltrimethylammonium bromide, 1g of tetraethyl orthosilicate, 1g of tetrabutyl titanate, 1g of 3-aminopropyltriethoxysilane, 1g of antioxidant 168 and 1g of epoxidized soybean oil.
[0027] The method for preparing the biodegradable material with added BBM bamboo powder comprises the following steps: S1, sending bamboo powder into a low-temperature oxygen plasma treatment instrument for treatment for 5s, the treatment power is 100W, adding dopamine hydrochloride to 50g Tris-HCl buffer with a concentration of 0.01mol / L, ultrasonic treatment for 1h, the ultrasonic frequency is 5kHz, using ammonia water to adjust the pH value of the system to 7.5-8.5, adjusting the temperature to 60°C, stirring at a speed of 100r / min for 10h, centrifuging, washing, and vacuum drying to obtain pretreated bamboo powder; S2. Add n-butylamine and hexadecyltrimethylammonium bromide to 10 g of water, stir at 80°C for 10 min at a stirring speed of 100 r / min, add tetraethyl orthosilicate, continue stirring for 10 min, add tetrabutyl titanate, continue stirring for 1 h, centrifuge, wash with ethanol, add 10 g of methanol and 1 g of 30% concentrated hydrochloric acid by mass, reflux in an oil bath for 1 h, centrifuge, wash with ethanol, vacuum dry, send to a tubular furnace for calcination, add 3-aminopropyltriethoxysilane and 10 g of anhydrous ethanol, stir at 40°C for 1 h, centrifuge, wash with ethanol, and vacuum dry to obtain activated titanium dioxide; S3, polybutylene adipate-terephthalate, polybutylene succinate, pretreated bamboo powder, activated titanium dioxide, antioxidant 168, and epoxidized soybean oil are mixed, and the mixture is fed into a twin-screw extruder for extrusion. The extrusion temperature of the twin-screw extruder is 190° C., and the main screw speed is 400 rpm. Example 2
[0028] A biodegradable material with BBM bamboo powder added, the raw materials of which include: 30g of polybutylene adipate-terephthalate, 20g of polybutylene succinate, 20g of bamboo powder, 3g of dopamine hydrochloride, 0.5g of n-butylamine, 2g of hexadecyltrimethylammonium bromide, 5g of tetraethyl orthosilicate, 2g of tetrabutyl titanate, 2g of 3-aminopropyltriethoxysilane, 2g of antioxidant DNP, and 2g of dibutyltin dilaurate.
[0029] The method for preparing the biodegradable material with added BBM bamboo powder comprises the following steps: S1. Send bamboo powder into a low-temperature oxygen plasma treatment instrument for treatment for 15 seconds, with a treatment power of 150W, add dopamine hydrochloride to 100g of Tris-HCl buffer with a concentration of 0.05mol / L, and perform ultrasonic treatment for 2h at an ultrasonic frequency of 15kHz. Use ammonia water to adjust the pH value of the system to 7.5-8.5, adjust the temperature to 80°C, stir at a speed of 500r / min for 15h, centrifuge, wash, and vacuum dry to obtain pretreated bamboo powder; S2, adding n-butylamine and hexadecyltrimethylammonium bromide to 30g of water, stirring at 90°C for 20min, stirring at a speed of 500r / min, adding tetraethyl orthosilicate thereto, continuing stirring for 30min, adding tetrabutyl titanate thereto, continuing stirring for 2h, centrifuging, washing with ethanol, adding 20g of methanol and 3g of concentrated hydrochloric acid with a mass fraction of 35%, reflux in an oil bath for 2h, centrifuging, washing with ethanol, vacuum drying, sending into a tubular furnace for calcination, adding 3-aminopropyltriethoxysilane and 30g of anhydrous ethanol, stirring at 50°C for 2h, centrifuging, washing with ethanol, and vacuum drying to obtain activated titanium dioxide; S3, polybutylene adipate-terephthalate, polybutylene succinate, pretreated bamboo powder, activated titanium dioxide, antioxidant DNP, and dibutyltin dilaurate are mixed, and the mixture is fed into a twin-screw extruder for extrusion. The extrusion temperature of the twin-screw extruder is 210° C., and the main screw speed is 600 rpm. Example 3
[0030] A biodegradable material with BBM bamboo powder added, the raw materials of which include: 25g of polybutylene adipate-terephthalate, 12g of polybutylene succinate, 17g of bamboo powder, 1.5g of dopamine hydrochloride, 0.2g of n-butylamine, 1.7g of hexadecyltrimethylammonium bromide, 2g of tetraethyl orthosilicate, 1.7g of tetrabutyl titanate, 1.2g of 3-aminopropyltriethoxysilane, 1.7g of antioxidant DLTP and 1.2g of tricresyl phosphate.
[0031] The method for preparing the biodegradable material with added BBM bamboo powder comprises the following steps: S1, sending bamboo powder into a low-temperature oxygen plasma treatment instrument for treatment for 12 seconds, the treatment power is 110W, adding dopamine hydrochloride to 90g of Tris-HCl buffer with a concentration of 0.02mol / L, ultrasonic treatment for 100min, the ultrasonic frequency is 9kHz, the pH value of the system is adjusted to 7.5-8.5 with ammonia water, the temperature is adjusted to 75°C, stirring at a speed of 200r / min for 13h, centrifuging, washing, and vacuum drying to obtain pretreated bamboo powder; S2, adding n-butylamine and hexadecyltrimethylammonium bromide to 15g of water, stirring at 88°C for 12min, stirring at a speed of 400r / min, adding tetraethyl orthosilicate thereto, continuing stirring for 15min, adding tetrabutyl titanate thereto, continuing stirring for 100min, centrifuging, washing with ethanol, adding 12g of methanol and 2g of concentrated hydrochloric acid with a mass fraction of 32%, reflux in an oil bath for 100min, centrifuging, washing with ethanol, vacuum drying, sending into a tubular furnace for calcination, adding 3-aminopropyltriethoxysilane and 15g of anhydrous ethanol, stirring at 48°C for 80min, centrifuging, washing with ethanol, and vacuum drying to obtain activated titanium dioxide; S3, polybutylene adipate-terephthalate, polybutylene succinate, pretreated bamboo powder, activated titanium dioxide, antioxidant DLTP, and tricresyl phosphate are mixed, and the mixture is fed into a twin-screw extruder for extrusion. The extrusion temperature of the twin-screw extruder is 205° C., and the main screw speed is 450 rpm. Example 4
[0032] A biodegradable material with BBM bamboo powder added, the raw materials of which include: 15g of polybutylene adipate-terephthalate, 18g of polybutylene succinate, 13g of bamboo powder, 2.5g of dopamine hydrochloride, 0.4g of n-butylamine, 1.3g of hexadecyltrimethylammonium bromide, 4g of tetraethyl orthosilicate, 1.3g of tetrabutyl titanate, 1.8g of 3-aminopropyltriethoxysilane, 1.3g of antioxidant 1010, and 1.8g of acetyl tributyl citrate.
[0033] The method for preparing the biodegradable material with added BBM bamboo powder comprises the following steps: S1, sending bamboo powder into a low-temperature oxygen plasma treatment instrument for 8 seconds, the treatment power is 130W, adding dopamine hydrochloride to 70g of Tris-HCl buffer with a concentration of 0.04mol / L, ultrasonic treatment for 80min, the ultrasonic frequency is 12kHz, the pH value of the system is adjusted to 7.5-8.5 with ammonia water, the temperature is adjusted to 65°C, stirring at a speed of 400r / min for 11h, centrifuging, washing, and vacuum drying to obtain pretreated bamboo powder; S2, adding n-butylamine and hexadecyltrimethylammonium bromide to 25g of water, stirring at a temperature of 82°C for 18min, stirring at a speed of 200r / min, adding tetraethyl orthosilicate thereto, continuing stirring for 25min, adding tetrabutyl titanate thereto, continuing stirring for 80min, centrifuging, washing with ethanol, adding 18g of methanol and 2g of concentrated hydrochloric acid with a mass fraction of 32%, reflux in an oil bath for 80min, centrifuging, washing with ethanol, vacuum drying, sending into a tubular furnace for calcination, adding 3-aminopropyltriethoxysilane and 25g of anhydrous ethanol, stirring at a temperature of 42°C for 100min, centrifuging, washing with ethanol, and vacuum drying to obtain activated titanium dioxide; S3, polybutylene adipate-terephthalate, polybutylene succinate, pretreated bamboo powder, activated titanium dioxide, antioxidant 1010, and acetyl tributyl citrate are mixed, and the mixture is fed into a twin-screw extruder for extrusion. The extrusion temperature of the twin-screw extruder is 195° C., and the main screw speed is 550 rpm. Example 5
[0034] A biodegradable material with BBM bamboo powder added, the raw materials of which include: 20g of polybutylene adipate-terephthalate, 15g of polybutylene succinate, 15g of bamboo powder, 2g of dopamine hydrochloride, 0.3g of n-butylamine, 1.5g of hexadecyltrimethylammonium bromide, 3g of tetraethyl orthosilicate, 1.5g of tetrabutyl titanate, 1.5g of 3-aminopropyltriethoxysilane, 1.5g of antioxidant BHT, and 1.5g of acetyl tributyl citrate.
[0035] The method for preparing the biodegradable material with added BBM bamboo powder comprises the following steps: S1, sending bamboo powder into a low-temperature oxygen plasma treatment instrument for treatment for 10 seconds, the treatment power is 120W, adding dopamine hydrochloride to 80g of Tris-HCl buffer with a concentration of 0.03mol / L, ultrasonic treatment for 90min, the ultrasonic frequency is 10.5kHz, the pH value of the system is adjusted to 7.5-8.5 with ammonia water, the temperature is adjusted to 70°C, stirring at a speed of 300r / min for 12h, centrifuging, washing, and vacuum drying to obtain pretreated bamboo powder; S2, adding n-butylamine and hexadecyltrimethylammonium bromide to 20g of water, stirring at a temperature of 85°C for 15min, stirring at a speed of 300r / min, adding tetraethyl orthosilicate thereto, continuing stirring for 20min, adding tetrabutyl titanate thereto, continuing stirring for 90min, centrifuging, washing with ethanol, adding 15g of methanol and 2g of concentrated hydrochloric acid with a mass fraction of 32%, reflux in an oil bath for 90min, centrifuging, washing with ethanol, vacuum drying, sending into a tubular furnace, calcining at a temperature of 580°C for 3h, adding 3-aminopropyltriethoxysilane and 20g of anhydrous ethanol, stirring at a temperature of 45°C for 90min, centrifuging, washing with ethanol, and vacuum drying to obtain activated titanium dioxide; S3, polybutylene adipate-terephthalate, polybutylene succinate, pretreated bamboo powder, activated titanium dioxide, antioxidant BHT, and acetyl tributyl citrate are mixed, and the mixture is fed into a twin-screw extruder for extrusion. The extrusion temperature of the twin-screw extruder is 200° C., and the main screw speed is 500 rpm.
[0036] Comparative Example 1 A biodegradable material with BBM bamboo powder added, the raw materials of which include: 20g of polybutylene adipate-terephthalate, 15g of polybutylene succinate, 15g of bamboo powder, 2g of dopamine hydrochloride, 0.3g of n-butylamine, 1.5g of hexadecyltrimethylammonium bromide, 3g of tetraethyl orthosilicate, 1.5g of tetrabutyl titanate, 1.5g of 3-aminopropyltriethoxysilane, 1.5g of antioxidant BHT, and 1.5g of acetyl tributyl citrate.
[0037] The method for preparing the biodegradable material with added BBM bamboo powder comprises the following steps: S1. Add bamboo powder and dopamine hydrochloride to 80 g of Tris-HCl buffer with a concentration of 0.03 mol / L, perform ultrasonic treatment for 90 min, the ultrasonic frequency is 10.5 kHz, the pH value of the system is adjusted to 7.5-8.5 with ammonia water, the temperature is adjusted to 70°C, stirred at a speed of 300 r / min for 12 h, centrifuged, washed, and vacuum dried to obtain pretreated bamboo powder; S2, adding n-butylamine and hexadecyltrimethylammonium bromide to 20g of water, stirring at a temperature of 85°C for 15min, stirring at a speed of 300r / min, adding tetraethyl orthosilicate thereto, continuing stirring for 20min, adding tetrabutyl titanate thereto, continuing stirring for 90min, centrifuging, washing with ethanol, adding 15g of methanol and 2g of concentrated hydrochloric acid with a mass fraction of 32%, reflux in an oil bath for 90min, centrifuging, washing with ethanol, vacuum drying, sending into a tubular furnace, calcining at a temperature of 580°C for 3h, adding 3-aminopropyltriethoxysilane and 20g of anhydrous ethanol, stirring at a temperature of 45°C for 90min, centrifuging, washing with ethanol, and vacuum drying to obtain activated titanium dioxide; S3, polybutylene adipate-terephthalate, polybutylene succinate, pretreated bamboo powder, activated titanium dioxide, antioxidant BHT, and acetyl tributyl citrate are mixed, and the mixture is fed into a twin-screw extruder for extrusion. The extrusion temperature of the twin-screw extruder is 200° C., and the main screw speed is 500 rpm.
[0038] Comparative Example 2 A biodegradable material with BBM bamboo powder added, the raw materials of which include: 20g of polybutylene adipate-terephthalate, 15g of polybutylene succinate, 15g of bamboo powder, 2g of dopamine hydrochloride, 0.3g of n-butylamine, 1.5g of hexadecyltrimethylammonium bromide, 3g of tetraethyl orthosilicate, 1.5g of tetrabutyl titanate, 1.5g of 3-aminopropyltriethoxysilane, 1.5g of antioxidant BHT, and 1.5g of acetyl tributyl citrate.
[0039] The method for preparing the biodegradable material with added BBM bamboo powder comprises the following steps: S1, sending bamboo powder into a low-temperature oxygen plasma treatment instrument for treatment for 10 seconds, the treatment power is 120W, adding dopamine hydrochloride to 80g of Tris-HCl buffer with a concentration of 0.03mol / L, ultrasonic treatment for 90min, the ultrasonic frequency is 10.5kHz, the pH value of the system is adjusted to 7.5-8.5 with ammonia water, the temperature is adjusted to 70°C, stirring at a speed of 300r / min for 12h, centrifuging, washing, and vacuum drying to obtain pretreated bamboo powder; S2, adding n-butylamine and hexadecyltrimethylammonium bromide to 20g of water, stirring at 85°C for 15min, stirring at a speed of 300r / min, adding tetrabutyl titanate thereto, stirring for 90min, centrifuging, washing with ethanol, adding 15g of methanol and 2g of concentrated hydrochloric acid with a mass fraction of 32%, reflux in an oil bath for 90min, centrifuging, washing with ethanol, vacuum drying, sending into a tubular furnace, calcining at a temperature of 580°C for 3h, adding 3-aminopropyltriethoxysilane and 20g of anhydrous ethanol, stirring at a temperature of 45°C for 90min, centrifuging, washing with ethanol, and vacuum drying to obtain activated titanium dioxide; S3, polybutylene adipate-terephthalate, polybutylene succinate, pretreated bamboo powder, activated titanium dioxide, antioxidant BHT, and acetyl tributyl citrate are mixed, and the mixture is fed into a twin-screw extruder for extrusion. The extrusion temperature of the twin-screw extruder is 200° C., and the main screw speed is 500 rpm.
[0040] The tensile strength of the biodegradable materials obtained in Example 5 and Comparative Examples 1-2 was measured with reference to GB / T 1040.2-2022 “Determination of tensile properties of plastics Part 2: Test conditions for molded and extruded plastics”.
[0041] The flexural strength of the biodegradable materials obtained in Example 5 and Comparative Examples 1-2 was measured with reference to GB / T 9341-2008 “Determination of flexural properties of plastics”.
[0042] The notched impact strength of the biodegradable materials obtained in Example 5 and Comparative Examples 1-2 was measured with reference to GB / T 1043.1-2008 “Determination of impact properties of simply supported beams of plastics Part 1: Non-instrumented impact test”.
[0043] Subsequently, referring to GB / T 14522-2008 "Artificial weathering test method for plastics, coatings and rubber materials for mechanical industrial products - fluorescent ultraviolet lamp", the biodegradable materials obtained in Example 5 and Comparative Examples 1-2 were placed in an ultraviolet aging test chamber for treatment at an irradiation intensity of 0.82 W / m 2, constant temperature 32℃, total irradiation time 240h; exposure period 8h drying, 4h condensation. The tensile strength, bending strength and impact strength of each group of samples after UV aging were measured again, and the retention rate of each strength was calculated.
[0044] Strength retention rate = strength after UV aging ÷ strength before UV aging × 100% like Figure 1-Figure 3 As shown, the tensile strength, flexural strength, notched impact strength and various strength retention rates of the biodegradable material obtained in Example 5 are the highest, which are better than those of Comparative Examples 1-2 (P < 0.05).
[0045] The biodegradable materials obtained in Example 5 and Comparative Examples 1-2 were made into standard specimens of 100 mm×10 mm×1.0 mm, and the weight of each standard specimen was weighed and recorded; then the standard specimens were respectively wrapped in gauze and buried in the soil 20 cm from the ground surface; after 60 days, they were taken out, washed, dried, weighed and recorded, and the 60-day weight loss rate was calculated. The number of days required for complete degradation was then tested, and complete degradation was considered when the weight loss rate reached 98%.
[0046] 60-day weight loss rate (%) = (weight before test - weight after 60 days of burial in the soil) ÷ weight before test × 100% like Figure 4 As shown, the 60-day weight loss rate of the biodegradable materials obtained in Example 5 and Comparative Examples 1-2 can be degraded by more than 75% in 60 days, and can be completely degraded within 130 days, which proves that all three have excellent biodegradability.
[0047] The degradation period of the invention after being discarded is short, and the invention has a very good prospect for being used in beer bottles.
[0048] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A biodegradable material with added BBM bamboo powder, characterized in that: The raw materials include, by mass, 10-20 parts of polybutylene succinate, 10-30 parts of polybutylene adipate-terephthalate, 10-20 parts of bamboo powder, 1-3 parts of dopamine hydrochloride, 0.1-0.5 parts of n-butylamine, 1-2 parts of hexadecyltrimethylammonium bromide, 1-5 parts of tetraethyl orthosilicate, 1-2 parts of tetrabutyl titanate, 1-2 parts of 3-aminopropyltriethoxysilane, 1-2 parts of antioxidant and 1-2 parts of plasticizer.
2. The biodegradable material with added BBM bamboo powder according to claim 1, characterized in that: The antioxidant is at least one of antioxidant BHT, antioxidant DNP, antioxidant DLTP, antioxidant 1010, and antioxidant 168.
3. The biodegradable material with added BBM bamboo powder according to claim 1, characterized in that: The plasticizer is at least one of disproportionated rosin, epoxidized soybean oil, dibutyltin dilaurate, acetyl tributyl citrate, and tricresyl phosphate.
4. The biodegradable material with added BBM bamboo powder according to claim 1, characterized in that: The mesh size of bamboo powder is 1000-2000 mesh.
5. The biodegradable material with added BBM bamboo powder according to claim 1, characterized in that: The bamboo powder is obtained by crushing, extracting, filtering, concentrating, refining, purifying, drying and crushing the moso bamboo with an age of 3 to 3.5 years.
6. A method for preparing a biodegradable material with BBM bamboo powder added as claimed in any one of claims 1 to 5, characterized in that: The steps include: S1. Treat bamboo powder with low-temperature oxygen plasma for 5-15 seconds, with the treatment power of oxygen plasma being 100-150W, then add it and dopamine hydrochloride into Tris-HCl buffer, perform ultrasonic treatment for 1-2 hours, adjust the pH value of the system to 7.5-8.5, stir at 60-80° C. for 10-15 hours, centrifuge, wash, and vacuum dry to obtain pretreated bamboo powder; S2, adding n-butylamine and hexadecyltrimethylammonium bromide to water, stirring at 80-90°C for 10-20min, adding tetraethyl orthosilicate thereto and continuing stirring for 10-30min, adding tetrabutyl titanate thereto and continuing stirring for 1-2h, centrifuging, washing, adding methanol and concentrated hydrochloric acid, reflux in an oil bath for 1-2h, centrifuging, washing with ethanol, vacuum drying, sending into a tubular furnace for calcination, adding 3-aminopropyltriethoxysilane and anhydrous ethanol, stirring at 40-50°C for 1-2h, centrifuging, washing, and vacuum drying to obtain activated titanium dioxide; S3, mixing polybutylene adipate-terephthalate, polybutylene succinate, pretreated bamboo powder, activated titanium dioxide, antioxidant and plasticizer, and extruding.
7. The method for preparing the biodegradable material with added BBM bamboo powder according to claim 6, characterized in that: In S1, the concentration of Tris-HCl buffer is 0.01-0.05 mol / L.
8. The method for preparing biodegradable materials with added BBM bamboo powder according to claim 6, characterized in that: In S1, the ultrasound frequency is 5-15kHz.
9. The method for preparing biodegradable materials with added BBM bamboo powder according to claim 6, characterized in that: In S2, the calcination temperature is 550-600°C, and the calcination time is 2-4h.
10. Use of the biodegradable material with added BBM bamboo powder as claimed in any one of claims 1 to 5 as beer packaging material.
Citation Information
Patent Citations
Ultraviolet screening agent, preparation method thereof, polylactic acid film containing ultraviolet screening agent and preparation method of polylactic acid film
CN104845301A
Technique for improving interfacial compatibility of bamboo fiber and polybutylene succinate based on polydopamine bionic interfacial modification modifier
CN107459830A
Mildew-proof and corrosion-proof bamboo-plastic composite material and preparation method thereof
CN117186528A
Method for preparing biodegradable material by taking PBS (Phosphate Buffer Solution) as matrix
CN117467252A
Preparation method of TiO2-coated SiO2 material
CN119114044A
Cited By
Bamboo powder bio-based degradable material and preparation method thereof
CN120842874A
Durable sound insulation tile adhesive and preparation method thereof
CN121406246A
Durable soundproof ceramic tile adhesive and method for preparing the same
CN121406246B